Interview with Coordinators: Aline Monçores e Deborah Christo (Revista de Ensino em Artes, Moda e Design, 2022)
Interview with WG12 coordinators, held between July and August 2022, from the cities of Florianópolis and Rio de Janeiro
Keywords: Critical theory; Fashion design; Design criticism